Crystal Growth of Semiconductor CuAl0.4Ti0.6Se2 and studding the Structural Properties of its Alloy and Thin Film - Abdul-Kadom, Arshad H. (Iraqi Journal of Physics, 2009)
Tetragonal compound CuAl0.4Ti0.6Se2 semiconductor has been prepared bymelting the elementary elements of high purity in evacuated quartz tube under lowpressure 10-2 mbar and temperature 1100 oC about 24 hr. Single crystal has beengrowth from this compound using slowly cooled average between (1-2) C/hr , alsothin films have been prepared using thermal evaporation technique and vacuum 10-6mbar at room temperature .The structural properties have been studied for the powderof compound of CuAl0.4Ti0.6Se2u using X-ray diffraction (XRD) . The structure of thecompound showed chalcopyrite structure with unite cell of right tetragonal anddimensions of a=11.1776 Ao ,c=5.5888 Ao .The structure of thin films showedamorphous structure and the films have crystallized under annealing treatment in therange of temperature (150-300) oC.